2018
DOI: 10.1002/aic.16056
|View full text |Cite
|
Sign up to set email alerts
|

Toward a continuous synthesis of porous carbon xerogel beads

Abstract: A continuous process for producing porous carbon xerogel beads has been developed. It consists in injecting a pre‐cured aqueous solution of resorcinol and formaldehyde on top of a column filled with hot oleic acid. The latter is pumped on the top of the column and fed at the bottom, generating an upward flow that can be adjusted to match the terminal velocity of the settling beads. Thus, the bead residence time in the column can be adjusted to match the gelation time, allowing the beads to solidify before reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…In the present work, above a pH of 7, the structure of the CXG collapses, with this pH value being higher than the pH value at which collapse occurs in other studies reported in the literature (around pH 6–6.5) [ 66 , 70 ]. This indicates that the synthesis conditions followed in this work (solvent exchange and sub-critical drying) avoid collapse in syntheses at higher pHs, thus obtaining CXG with higher S BET values (696 m 2 g −1 for CXG-7) than those reported in the literature [ 71 , 72 , 73 , 74 ]. Although CXG-7 presents the highest surface area values, its pore volume values are lower, due to its narrower pores.…”
Section: Resultsmentioning
confidence: 58%
“…In the present work, above a pH of 7, the structure of the CXG collapses, with this pH value being higher than the pH value at which collapse occurs in other studies reported in the literature (around pH 6–6.5) [ 66 , 70 ]. This indicates that the synthesis conditions followed in this work (solvent exchange and sub-critical drying) avoid collapse in syntheses at higher pHs, thus obtaining CXG with higher S BET values (696 m 2 g −1 for CXG-7) than those reported in the literature [ 71 , 72 , 73 , 74 ]. Although CXG-7 presents the highest surface area values, its pore volume values are lower, due to its narrower pores.…”
Section: Resultsmentioning
confidence: 58%
“…For this reason, new forms of N-doped porous carbons are actively sought. Carbon gels remain at the center of researchers’ attention due to their unique porous structure and ease of preparation [ 31 , 32 ]. Here, we proposed another versatile approach to synthesize microporous carbons with a high number of heteroatoms, which can easily be obtained from porous organic polymers.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that in order to use CXs on an industrial scale, the development of large-scale synthesis methods is required. Thus, a continuous process for the production of CX granules was proposed by Eskenazi et al [59]. In this process, an aqueous solution of resorcinol and formaldehyde is introduced into a column filled with hot oleic acid.…”
Section: Drying Stagementioning
confidence: 99%